Ovarian Tube Abscess in an Intrauterine Contraceptive Device User for 5 Years: A Case Report - Athira Fitri Kemalasari; Palupi Widiasih (Journal of Social Research, 2023)
A tubo-ovarian abscess (TOA) is one of the late complications of untreated Pelvic Inflammatory Disease (PID) and can be life-threatening if the abscess ruptures and results in sepsis.1 It most commonly affects women of reproductive age and nearly 60% of women with TOA are nulliparous.2 The association between tubo-ovarian abscess formation and the presence of an intrauterine device (IUD) is well recognized. It has been suggested that the risk of upper genital tract infection is highest during the immediate period following the insertion of an IUD. We report a case of pelvic inflammatory disease in a 44-year-old woman using an intrauterine contraceptive device (IUD) for more than 5 years, who complained of lower abdominal pain and lumbar pain without fever, and also had a thick-white vaginal discharge. The clinical diagnosis was performed by anamnesis and ultrasound (we found an hypo- hyperechoic mass on the right adnexa size 4.4 x 3.6 x 4.0 cm) and then the patient was treated with triple antibiotics for 3 days. Afterward, the patient was performed using exploring laparoscopy to continue to right salpingo-oophorectomy adhesiolysis left tubectomy, and IUD removal as well. Long-term users of IUDs remain at risk for serious pelvic infections. Every IUD user's patient should be routinely counseled by their gynecologist and tubo-ovarian abscess should be strongly considered in the differential diagnosis of an IUD user who presents with an adnexal mass, abdominal pain, and lumbar pain. The treatment must be a combination of antibiotics and surgery.